Optogenetically induced sleep spindle rhythms alter sleep architectures in mice - Kim, Angela; Latchoumane, Charles; Lee, Soojung; Kim, Guk Bae; Cheong, Eunji; Augustine, George J.; Shin, Hee-Sup (NATL ACAD SCIENCES, 2012)
Sleep spindles are rhythmic patterns of neuronal activity generated within the thalamocortical circuit. Although spindles have been hypothesized to protect sleep by reducing the influence of external stimuli, it remains to be confirmed experimentally whether there is a direct relationship between sleep spindles and the stability of sleep. We have addressed this issue by using in vivo photostimulation of the thalamic reticular nucleus of mice to generate spindle oscillations that are structurally and functionally similar to spontaneous sleep spindles. Such optogenetic generation of sleep spindles increased the duration of non-rapid eye movement (NREM) sleep. Furthermore, the density of sleep spindles was correlated with the amount of NREM sleep. These findings establish a causal relationship between sleep spindles and the stability of NREM sleep, strongly supporting a role for the thalamocortical circuit in sleep regulation.
Keywords: THALAMIC RETICULAR NUCLEUS; LESS-THAN-1 HZ OSCILLATION; CALCIUM-CHANNEL; NEURONS; STATES; MODES; WAVES; BURST